Hikmah Puasa Dalam Meningkatkan Kualitas Keimanan dan Ketaqwaan Umat Muslim - N, Nurmaini (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Ramadan fasting creates lifestyle changes for those who do it, many physical benefits have been produced by researchers. It is interesting how Ramadan fasting changes the dimensions of faith, so this study aims to explore Ramadan fasting as a reclamation of faith. This article is the result of findings from a qualitative literature research type, taking the theory of reclamation related to faith, then analyzed inductively to produce conclusions. The results of the study show: Ramadan fasting is a reclamation of faith where the command is intended for people who believe to become pious individuals both in individual and social dimensions, manifested in changes and increased faith towards a better and more meaningful direction in their lives. The implications of the research on the importance of faith are manifested in real behavior in the reality of life, more detailed indicators of increased faith in Ramadan fasting require further research.